Cytomorphological spectrum of scalp lesions in the population of a developing country: A retrospective study. Issue 6 (13th February 2019) - Sharma, Pooja; Pathak, Priya; Goyal, Aditi; Sharma, Sonal
Abstract : BACKGROUND: Scalp lesions are frequently encountered in clinical practice. Fine‐needle aspiration cytology (FNAC) can characterize most of these lesions; however, there is little published work on cytology of scalp lesions. METHODS: Records of all the patients subjected to FNAC from January 2011 to August 2016 were retrieved from the archives of the Cytopathology section of our Institute. Out of the 71 852 cases reviewed, 896 patients, who presented with palpable scalp lesions, were included in the study. Aspirates were obtained with a 23‐gauge needle attached to a 10 mL disposable plastic syringe. May–Grünwald–Giemsa stained and Pap stained slides were prepared. Special stains and immunocytochemical analysis were done when necessary. RESULTS: Out of the 896 cases of aspirates from scalp lesions, 155 (17.2%) aspirates were found to be inadequate for diagnosis. One hundred and fifty‐seven (21%) out of 741 adequate aspirates showed features of inflammatory or reactive pathology comprising of abscesses (57), cystic lesions (24), tubercular lesions (16), and reactive lymphadenopathy (66). Four hundred and fifteen (56%) aspirates revealed a tumor‐like etiology comprising of epidermal cyst (395), sebaceous cyst (4), dermoid cyst (1), calcinosis (7), vascular malformation (7), hematoma (5), and juvenile xanthogranulomatous lesion (1). Tumorous lesions formed 22.3% of the aspirates. Of these, 7 cases (4.2%) were of metastases to the scalp. CONCLUSION: In a developing country, FNAC is a useful and cost‐effective investigation for the diagnosis of a wide spectrum of scalp lesions. It allows rapid diagnosis and permits timely intervention thereby preventing complications due to delay in diagnosis.